Sistem Informasi Akuntansi Sebagai Infrastruktur Berkelanjutan: Analisis Kesiapan dan Tantangan Institusional di Indonesia - Gita Apsari Dewi (Politeknik Ganesha Medan, 2026)
The growing reliance on ESG reporting exposes a theoretical tension between Accounting Information Systems (AIS), which are designed for financial accountability, and sustainability reporting, which demands multidimensional, forward-looking, and verifiable information. The theoretical problem addressed in this study lies in the insufficient theorization of AIS readiness for ESG reporting within existing accounting and information systems literature. While sustainability studies emphasize disclosure quality, they largely overlook the internal system capacities that produce ESG data, creating a critical conceptual gap. This study investigates how AIS readiness for ESG reporting is shaped by technological, organizational, environmental, and ESG data capability factors in the Indonesian context. Using a qualitative descriptive methodology, the study applies content analysis to sustainability reports, annual reports, regulatory texts, and prior empirical research from 2020–2023. The findings reveal that AIS readiness remains fragmented, as ESG data capabilities are weakly embedded within core systems and lack systematic audit trails. This study contributes by reconceptualizing AIS readiness as a system-level condition for sustainability accountability. This research extends AIS and sustainability reporting literature by modifying the Technology Organization Environment (TOE) framework through the explicit inclusion of ESG data capability as a mediating construct. This study matters because without theoretically grounded system readiness, ESG reporting risks remaining symbolic rather than substantively accountable